Factors predicting in-hospital all-cause mortality in COVID 19 patients at the Laquintinie Hospital Douala, Cameroon. Issue 47 (May 2022) - Ebongue, Marie Solange Ndom; Lemogoum, Daniel; Endale-Mangamba, Laurent Mireille; Barche, Blaise; Eyoum, Christian; Simo Yomi, Styve Hermane; Mekolo, David; Ngambi, Vincent; Doumbe, Jacques; Sike, Christiane Medi; Boombhi, Jerome; Ngondi, Grace; et al.
Abstract: Background: Despite being a global pandemic, little is known about the factors influencing in-hospital mortality of COVID-19 patients in sub-Saharan Africa. This study aimed to provide data on in-hospital mortality among COVID-19 patients hospitalized in a single large center in Cameroon. Methods: A hospital-based prospective follow-up was conducted from March 18 to June 30, 2020, including patients >18 years with positive PCR for SARS-COV-2 on nasopharyngeal swab admitted to the Laquintinie Douala hospital COVID unit. Predictors of in-hospital mortality were assessed using Kaplan Meir survival curves and Weibull regression for the accelerated time failure model. Statistical significance was considered as p < 0.05. Results: Overall 712 patients (65, 7% men) were included, mean age 52, 80 ± 14, 09 years. There were 580 (67, 8% men) in-hospital patients. The median duration of hospital stay was eight days. The in-hospital mortality was 22.2%. Deceased patients compared to survivors were significantly older, had a higher temperature, respiratory rate, and heart rate, and lowest peripheral oxygen saturation at admission. After adjusting for age, sex, and other clinical patient characteristics, increased heart rate, increased temperature, decreased peripheral oxygen saturation. The critical clinical status was significantly associated with increased in-hospital mortality. In contrast, hospitalization duration greater than eight days and the use of hydroxychloroquine (HCQ) + azithromycin (AZM) therapy was associated with decreased risk of in-hospital mortality. Conclusion: One in five hospitalized COVID-19 patients die in a low-middle income setting. Critical clinical status, dyspnea, and increased heart rate were predictors of in-hospital mortality. This study will serve as a prerequisite for more robust subsequent follow-up studies. Also, these results will aid in revising national guidelines for the management of COVID-19 in Cameroon.